Responsivitas dan Koordinasi KPU Kota Jambi dalam Verifikasi Dukungan Bakal Calon Anggota DPD RI pada Pemilu 2024 - Juliana Presenia Pardede; Nasuhaidi Nasuhaidi; Zakly Hanafi Ahmad (Indo Publishing, 2026)
This study examines how the General Election Commission (KPU) of Jambi City developed responsiveness and coordination in verifying support for prospective candidates for the Regional Representative Council of the Republic of Indonesia (DPD RI) in the 2024 General Election. The study is grounded in the importance of support verification as a stage that determines the validity of independent candidacy, as well as in continuing problems related to data accuracy, procedural consistency, inter-organizational coordination, and the use of the Candidate Information System (SILON). This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, document analysis, and limited observation, and were analyzed through data reduction, data display, and conclusion drawing. The findings show that support verification in Jambi City functioned not merely as an administrative procedure, but also as a practice of electoral governance that required rapid response, procedural accuracy, and consistent coordination among implementing actors. The responsiveness of KPU Jambi City was reflected in its prompt handling of verification findings and its provision of space for clarification, while coordination functioned as a mechanism for aligning work processes and controlling the quality of decisions. SILON contributed to administrative organization and data traceability, but its effectiveness remained dependent on operator capacity, technical readiness, and institutional coordination. This study concludes that the quality of support verification is determined not only by formal compliance with regulations, but also by the institutional capacity of election administrators to translate rules into responsive, coordinated, and accountable practices.